PENTINGNYA PENDIDIKAN KARAKTER DI PERGURUAN TINGGI - Ika Widiastuti (Perkumpulan Dosen Program Hibah Indonesia, 2024)
The character of a community, especially the younger generation is the identity of the community itself, and the existence of a nation is determined by the character owned. The important role of young people in dealing with the problems in this era of globalization is the return builder character (character enablers), empowering character (character builders) and engineer character (character enginee). In general, the actual character of the Indonesian nation must be returned to the basic value of the Pancasila.Keywords: national character, the younger generation, moral decadence